2001
DOI: 10.1073/pnas.211297698
|View full text |Cite
|
Sign up to set email alerts
|

Monarch larvae sensitivity to Bacillus thuringiensis - purified proteins and pollen

Abstract: Laboratory tests were conducted to establish the relative toxicity of Bacillus thuringiensis (Bt) toxins and pollen from Bt corn to monarch larvae. Toxins tested included Cry1Ab, Cry1Ac, Cry9C, and Cry1F. Three methods were used: (i) purified toxins incorporated into artificial diet, (ii) pollen collected from Bt corn hybrids applied directly to milkweed leaf discs, and (iii) Bt pollen contaminated with corn tassel material applied directly to milkweed leaf discs. Bioassays of purified Bt toxins indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
159
0
3

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(169 citation statements)
references
References 13 publications
7
159
0
3
Order By: Relevance
“…The potential hazard to nontarget Lepidoptera (risk hypothesis 4) was recognized initially but it was concluded that the risk is negligible 43 . Additional studies under more realistic exposure conditions were triggered once a note 44 and a more comprehensive study 45 had revealed a hazard of Cry1Ab to larvae of the monarch butterfly. Studies were conducted under semi-field conditions.…”
Section: Box 1 Evaluation Path For Bt Maize Expressing Cry1ab For Nonmentioning
confidence: 99%
“…The potential hazard to nontarget Lepidoptera (risk hypothesis 4) was recognized initially but it was concluded that the risk is negligible 43 . Additional studies under more realistic exposure conditions were triggered once a note 44 and a more comprehensive study 45 had revealed a hazard of Cry1Ab to larvae of the monarch butterfly. Studies were conducted under semi-field conditions.…”
Section: Box 1 Evaluation Path For Bt Maize Expressing Cry1ab For Nonmentioning
confidence: 99%
“…Later laboratory bioassays showed that the only transgenic Bt-maize pollen that consistently affected monarch larvae was pollen from Event 176, an event that has meanwhile been withdrawn from the market. The results suggested that pollen from the most widely planted Bt-maize events (MON810 and Bt 11) will have no acute effects on larvae in field settings [62,63] since their pollen expresses 80 times less toxin than Event 176 [63]. The results also suggested that pollen densities used by Losey et al [61] were in excess compared to pollen densities present in maize fields or that the pollen of event Bt 11 used may have been contaminated with non-pollen tissues [64].…”
Section: Effects Of Bt-crops On Butterfliesmentioning
confidence: 95%
“…The results also suggested that pollen densities used by Losey et al [61] were in excess compared to pollen densities present in maize fields or that the pollen of event Bt 11 used may have been contaminated with non-pollen tissues [64]. Excessive pollen densities of the currently commercialized events (Bt 11 and MON810) would be required to obtain relevant adverse effects on larval developments [62]. The critics also felt that in addition to the mere toxicity (hazard), an ecological risk assessment has to consider exposure, i.e., whether the monarch larvae will encounter the Bt-toxin and at what level.…”
Section: Effects Of Bt-crops On Butterfliesmentioning
confidence: 95%
“…R ecent public concerns over the transgenic (genetically modified) plants and nontarget impacts such as those from Bttoxin expressing corn pollen on the monarch butterfly populations have escalated, despite good pest management intentions and good science (1)(2)(3)(4)(5)(6)(7)(8)(9). Plant resistance to insect pests has evolved naturally over many millions of years and involves (i) both constitutive and inducible phytochemical and morphological mechanisms in plants, (ii) counteradaptations to plant defenses by the herbivores, and (iii) biotic interactions of the multitrophic level communities of insect pathogens, parasites, and predators (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…It seems clear, for various reasons described in the six articles that recently appeared in PNAS (1)(2)(3)(4)(5)(6), that the risks to nontarget lepidopterans of Bt toxins in corn pollen are significantly less than those involved with aerial application of Bt sprays for gypsy moths. It may be that much of the concern about Btk corn pollen deals more with perceived risks than with realized and potential risks (34).…”
mentioning
confidence: 99%